Reliability of fully automated versus visually controlled pre- and post-processing of resting-state EEG. Issue 2 (February 2015) - Hatz, F.; Hardmeier, M.; Bousleiman, H.; Rüegg, S.; Schindler, C.; Fuhr, P.
Highlights Automated processing of resting state quantitative EEG is as reliable as visually controlled processing. Reduced inter-rater reliability is avoided by automated EEG processing. Automated processing of EEG is less time consuming and reduces the need for trained raters.